2017
DOI: 10.1177/0022034517717255
|View full text |Cite
|
Sign up to set email alerts
|

Ras Signaling Regulates Stem Cells and Amelogenesis in the Mouse Incisor

Abstract: The role of Ras signaling during tooth development is poorly understood. Ras proteins-which are activated by many upstream pathways, including receptor tyrosine kinase cascades-signal through multiple effectors, such as the mitogen-activated protein kinase (MAPK) and PI3K pathways. Here, we utilized the mouse incisor as a model to study how the MAPK and PI3K pathways regulate dental epithelial stem cells and amelogenesis. The rodent incisor-which grows continuously throughout the life of the animal due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Ras signaling is activated after FGFs bind to receptor tyrosine kinases (RTKs) and then regulate the proliferative activity of DESCs through the mitogen-activated protein kinase (MAPK) and phosphatidylinositol 3-kinase (PI3K) pathways. Further evidence about the role of MAPK and PI3K in amelogenesis has been proposed through a mouse incisor model of Ras dysregulation[ 57 ].…”
Section: Regulatory Network Of Descs In Mouse Incisorsmentioning
confidence: 99%
“…Ras signaling is activated after FGFs bind to receptor tyrosine kinases (RTKs) and then regulate the proliferative activity of DESCs through the mitogen-activated protein kinase (MAPK) and phosphatidylinositol 3-kinase (PI3K) pathways. Further evidence about the role of MAPK and PI3K in amelogenesis has been proposed through a mouse incisor model of Ras dysregulation[ 57 ].…”
Section: Regulatory Network Of Descs In Mouse Incisorsmentioning
confidence: 99%
“…This ectopic expression presents clear evidence for cell fate conversion and should contribute to the establishment of stem and progenitor cell compartments in the extra incisor crown (Sun et al 2016). Activation of mitogen-activated protein kinase (MAPK) cascade associated with ERK and the p38 kinases plays an important role in incisor formation and differentiation (Lee et al 2009; Greenblatt et al 2015; Zheng et al 2017). We found the ectopic presence of pERK and pP38 kinases in the region overlapping with Sox2 + cells in the lingual OEE (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This highlights the importance of cross-talk between the TGFβ, Wnt and FGF signaling pathways in regulating dental epithelium-mesenchyme interactions (Yang et al, 2014). It has also been shown that FGFs bind to receptor tyrosine kinases (RTKs) to activate Ras signaling, which signals through the MAPK and PI3K pathways to regulate epithelial stem cell maintenance and ameloblast differentiation in the adult mouse incisor (Zheng et al, 2017).…”
Section: The Regulation Of Dental Stem Cells During Tissue Homeostasis and Repairmentioning
confidence: 96%